A new polyoxygenated abietane diterpenoid from the rattans of Bauhinia championii (Benth.) Benth. Issue 21 (2nd November 2018) - Hua, Li-Ping; Zhang, Yu-Qin; Ye, Miao; Xu, Wen; Wang, Xiao-Ying; Fu, Yan-Hui; Xu, Wei
Abstract: A new polyoxygenated abietane diterpenoid, bauchampine A (1 ), together with seven known compounds (2 –8 ), were isolated from the rattans of Bauhinia championii (Benth.) Benth. The structure of1 was elucidated by extensive spectroscopic methods and the known compounds were identified by comparison with the data reported in the literature. New compound1 was evaluated for its anti-rheumatoid arthritis activity via examining its anti-proliferative effect on synoviocytes in vitro . Compound1 exhibited inhibitory effect on the proliferation of synoviocytes with IC50 value comparable to that of methotrexate. Abstract :